Analysis of Factors Influencing Visitor Arrivals at the Widuri Beach Tourist Attraction, Pemalang Regency - Rijal Gunawan W; Nugroho Sumarjiyanto Benedictus Maria (Cita konsultindo, 2026)
This study aims to analyze the factors influencing tourist visits to the Widuri Beach tourist attraction in Pemalang Regency. The research approach used is quantitative, with a survey method conducted on tourists visiting Widuri Beach. The research variables include components of tourist attraction, including attractions, facilities, accessibility, activities, supporting services, and tourist perceptions. The data obtained are analyzed using statistical methods to determine the influence of each variable on the level of tourist visits. This study also refers to the theory of tourism demand and consumer behavior to strengthen the analytical framework in the context of marine tourism in the northern coastal area of Central Java. The results of this study are expected to provide an empirical overview of the dominant factors influencing tourist visits toWiduri Beach and explain the causes of fluctuations in visitor numbers. The findings of this study are expected to provide academic contributions to the development of tourism studies, particularly those related to tourism demand in coastal destinations.